ANALYSIS OF MARKET RISK MANAGEMENT STRATEGY IN ISLAMIC BANK : Case Study at Bank Mega Syariah Indonesia - Azizah Shodiqoh Rafidah; Rokhmat Subagiyo; Binti Nur Asiyah (Airlangga International Journal of Islamic Economics and Finance, 2024)
Market risks is one of the risks in islamic banking that cannot be avoided. If Islamic banking cannot manage market risk properly, it will have an impact on bank profitability or even lead to other risks. Therefore, Islamic banking must create a market risk management strategy to achive suistaneble bussiness growth. This research made Bank Mega Syariah the locus of research. The research method used is qualitative research using the main data source, namely Bank Mega Syariah's 2023 annual report as well as the December 2023 risk exposure and capital report. The result of the research show that Bank Mega Syariah manages market risk based on its fund distribution portofolio, the majority of which is in the form of financing and partly in the form of sukuk securities as a liquidity reserve, does nor carry out over the counter trading activities for proprietary trading so market risk exposure is relatively low. The focus changing behaviour and maintaining customer trust when market benchmark interest rate increase, adjusted to majority of financing which has a fixed margin.